Images of the Peoples of the World Encountered by the Mongols in the Jamiʿ al-tawarikh. Issue 1 (2nd January 2019) - Ghiasian, Mohamad Reza
ABSTRACT: Four copies of the Jamiʿ al-tawarikh produced at Rashid al-Din's scriptorium survive: one in Arabic and three in Persian. These codices are fragments of the second volume, which include the history of the non-Mongol peoples of Eurasia, including Ughuz Turks, Chinese, Jews, Franks and Indians. Interestingly, all these manuscripts were in the possession of the Timurid ruler Shahrukh, who ordered his scriptorium to complete the three Persian copies. Considering the section on the history of other nations, none of the Persian copies remains intact, because these parts have been refurbished or completed in Shahrukh's workshop. These sections in the three Persian codices contain calligraphy and illustrations from both the Ilkhanid and Timurid periods. Since these manuscripts were produced in the royal workshops of the Ilkhanid and Timurid rulers, they reflect the different international relations of the time. These reflections are obvious in the nature, the number and the placement of the illustrations. This paper examines the foreign relations of Iran in the beginning of the fourteenth and fifteenth centuries via the codicological study of these manuscripts.